Answer:
then simply become a french fry lol
Step-by-step explanation:
Answer:
y=x/2-3/4
y=3x
Step-by-step explanation:
Answer:
<em>x = 2</em>
<em>divide each term by 3 and simplify.</em>
3) x² - 121 = 0
x² = 121
x' = +√121
x' = 11
_______________
x'' = - √121
x'' = -11
Solution ⇒ S{-11 ; 11 } or (x-11)(x+11)
4) 4x² + 144 = 0
4x² = -144
x² = -144 / 4
x² = -36
x = √-36
No solution ⇒ S = ∅
5) z²+10z+21 = 0
Δ = 10² - 4(1)(21)
Δ = 100 - 84
Δ = 16
x' = (-10+4) / 2 = -6/2 = -3
x'' = (-10-4) / 2 = -14/2 = -7
Solution ⇒ S{ -7 ; -3} or (x+3)(x+7)